﻿Laparoscopic hepatectomy for hepatolithiasis - Outcomes from a single institution in Vietnam - Nguyen, Thanh Xuan; Dang, Nhu Thanh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Background: Hepatolithiasis is still a common disease in Vietnam and many countries in Asia with high rates of residual stones and recurrence after treatment. Treatment of hepatolithiasis requires a careful selection and combination between surgical, endoscopic, and interventional treatment. The role of laparoscopy, especially in hepatectomy for hepatolithiasis remains unclear and controversial due to technical difficulties. Methods: Between January 2019 to December 2023, 41 patients with hepatolithiasis undergoing laparoscopic hepatectomy were enrolled. The general characteristics, intraoperative, and postoperative data were analyzed. Results: The mean age was 54.7 ± 13.3 (29 - 81) years; the female/male ratio was 2.2. 70.7% of patients had both intra- and extrahepatic duct stones. Left lateral sectionectomy was performed in (29 cases), followed by left hepatectomy (6 cases), right posterior sectionectomy (3 cases), and right hepatectomy (2 cases), and combined resection (1 case). 90.2% of patients underwent common bile duct exploration. Cholangioscopic exploration with/without laser lithotripsy was used in 70.7%. The median surgery time is 152 (70 - 280) minutes. Intraoperative blood transfusion was required in only 6 cases (14.6%). The mean time to bowel movement was 2.3 ± 0.6 days. The mean postoperative hospital stay was 9.1 ± 2.1 days. 14.3% of patients experienced postoperative complications, including wound infection 12.2%, fluid collection 7.3%, pleural effusion (4.9%) and bile leak 4.9%. The complete stone clearance rate was 92.7%. Conclusion: Laparoscopic liver resection, especially left lobectomy, is a safe and effective treatment for patients with hepatolithiasis.